2016
DOI: 10.2174/1566524016666160316145715
|View full text |Cite
|
Sign up to set email alerts
|

HOX Genes as Potential Markers of Circulating Tumour Cells

Abstract: Circulating tumour cells (CTCs) have significant diagnostic potential as they can reflect both the presence and recurrence of a wide range of cancers. However, this potential continues to be limited by the lack of robust and accessible isolation technologies. An alternative to isolation might be their direct detection amongst other peripheral blood cells, although this would require markers that allow them to be distinguished from an exceptionally high background signal. This review assesses the potential role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 47 publications
(50 reference statements)
0
14
0
Order By: Relevance
“…The differential expression of HOX genes in cancer make the products of these genes potential biomarkers for both diagnosis and prognosis, and for precision medicine applications such as predicting treatment response (reviewed by Morgan and El-Tanani, 2016 [ 36 ]). One of the best characterized examples is Engrailed-2 ( EN2 ), a gene that is very closely related to the HOX genes but which is not located within the 4 main chromosomal clusters described above [ 37 ].…”
Section: Hox Genes In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The differential expression of HOX genes in cancer make the products of these genes potential biomarkers for both diagnosis and prognosis, and for precision medicine applications such as predicting treatment response (reviewed by Morgan and El-Tanani, 2016 [ 36 ]). One of the best characterized examples is Engrailed-2 ( EN2 ), a gene that is very closely related to the HOX genes but which is not located within the 4 main chromosomal clusters described above [ 37 ].…”
Section: Hox Genes In Cancermentioning
confidence: 99%
“…HOX gene expression at the RNA level has also been shown to have prognostic significance in acute myeloid leukaemia (AML) [ 41 ], and in several solid malignancies including mesothelioma (HOXB4) [ 42 ], breast cancer (HOXB7) [ 43 ], ovarian cancer [ 44 ], oral squamous cell carcinoma (HOXD13) [ 45 ], thyroid cancer (HOXC10) [ 46 ], clear cell renal cell carcinoma (HOXC11) [ 47 ], gastric cancer (HOXC6) [ 48 ], and bladder cancer (HOXB13) [ 49 ]. Discreet patterns of HOX gene expression apparently exist within different types of cancer, indicating that they could be used to distinguish between cancer types when the primary tumour type is unknown, for example in circulating tumour cells (CTCs) [ 36 ].…”
Section: Hox Genes In Cancermentioning
confidence: 99%
“…Homeobox-containing genes are highly evolutionarily conserved; proteins encoded by homeobox-containing genes are important transcription factors that precisely regulate the differentiation of cells by specifically activating downstream genes (9,10). Studies have indicated that homeobox-containing genes serve key roles in the generation and differentiation of embryos and organs of organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that dysregulated HOX genes could cause abnormalities in the development and tissue formation, leading to cell malignant transformation and tumorigenesis 13 . Recent studies suggested that HOX family proteins could be used as biomarkers of circulating tumor cells 14 . The Homo sapiens HOXC10 is located on the chromosome 12, which was reported to relate with the development of various tumors including GC 15‐19 .…”
Section: Introductionmentioning
confidence: 99%